Petroleum Hydrocarbon Fingerprints of Water and Sediment Samples of Buffalo River Estuary in the Eastern Cape Province, South Africa - A. O. Adeniji; O. O. Okoh; A. I. Okoh (Journal of Analytical Methods in Chemistry)
Petroleum hydrocarbon status of the Buffalo River Estuary in East London, South Africa, was evaluated from January to May, 2016. Surface water and sediment samples were collected from five points in the estuary and extracted using standard methods. The extracts were subsequently analyzed by gas chromatography-flame ionization detection. Results showed that total petroleum hydrocarbon (TPH) varied from 7.65 to 477 μg/L in the water and 12.59 to 1,100 mg/kg in the sediments, with mean values of 146.50 ± 27.96 μg/L and 209.81 ± 63.82 mg/kg, respectively. Concentrations of TPH in the sediments correlated significantly with organic carbon (OC) in both seasons. TPH and OC levels were slightly lower in summer than in autumn in the two environmental matrices, and the average amount of TPH in the water samples collected from all the sampling stations was generally lower than the EU standard limit of 300 μg/L. However, the levels in the sediments exceeded the EGASPIN target value (50 mg/kg) for mineral oil but were below the intervention value (5,000 mg/kg), indicating a serious impact of industrial growth and urbanization on the area, although the n-alkane ratios and indexes used for source tracking revealed excessive flow from both natural and anthropogenic sources.